»Exposure« – Verletzlichkeit und das Politische in Zeiten radikaler Ungewissheit - Hentschel, Christine; Krasmann, Susanne (transcript, 2020)
The political of the present is articulated in moments of "exposure" - of revelation, of exposing oneself, of endangerment.